Administrative settlement of the tax dispute under Algerian legislation - Krikou, Feriel (Journal of Human Sciences, 2023)
Tax is of great importance because of its close association with the citizen within the framework of his legal system. Within the framework of achieving justice, every citizen should bear tax according to his cost capacity in order to achieve equality between legal positions between individuals before tax The tax legislator is required to follow special procedures before administration A complaint to the tax administration, which is considered a compulsory and obligatory measure to be taken by the taxpayer to settle certain legal situations, and therefore considered as a channel for dialogue between the taxpayer and the tax administration, including including the legislator, with the aim of allowing the administration to control itself, and to reduce the strong pressure which the judicial authorities undergo from such disputes which can be resolved at the level of the administration and allow the continuation of the dialogue, between the taxpayer and the tax administration on the other hand.